Critical analysis of audit committee reporting in national government departments - Moloi, Steven Tankiso Mthokozisi (Mednarodna revija za javno upravo, 2015)
The paper critically assesses audit committee reporting in South Africa's national government departments (NGDs). During the review, it was established that, from the regulatory perspective, there were limited guidelines relating to the extent and nature of information that should be reported on the audit committee reports, whereas the main contribution of the paper are uniform benchmark features of audit committee reporting in the South Africa's national government departments. These benchmark features (categories) were developed using an inductive or bottom up thematic analysis which was applied on the applicable regulations as well as on all NGD's annual reports to determine the comprehensive themes and patterns of audit committee reporting across the departments. It is recommended that those audit committees in NGDs that do not currently report on these themes should expand their reporting to be comprehensive by including these themes.Using the established benchmark features in the form of themes, audit committees reports were coded and analysed to determine the disclosure of information relating to these themes. It was found that majority of categories reported on audit committee reports and analysed lacked transparency as to the role of audit committees in providing oversight in the NGDs concerned. In addition to the recommended audit committee themes, the paper further recommends that audit committees in NGDs should also consider voluntary disclosing of some additional information on their oversight activities. Disclosure of additional voluntary information would improve the usefulness of audit committee reports as users of this information would gain and understanding of yearly audit committee activities as of the nature of oversight and strategic engagements audit committees would have had with the management as well. The potential benefit for users of audit committee reports in NGDs is envisaged as flexibility, exposure and access to different dimensions of information reported by different NGDs. The potential benefit for audit committee members is grounded on the users' perception of audit committee reports, in this instance, the improvement in perception on their independence.
Keywords: audit; državna uprava; Južna Afrika; national government departments; revizija; revizijska poročila; South Africa